Characteristics Of Leachate Generated At Landfill Sites And Probable Risks Of Surface And Groundwater Pollution In The Surrounding Areas : A Case Study Of Matuail Landfill Site, Dhaka (Journal of Bangladesh Academy of Sciences, 2012)
The characteristics of leachate and its probable risks on surface and groundwater pollution were investigated following the analysis of some chemical parameters of the leachate generated in the Matuail landfill site, Dhaka, Bangladesh. The laboratory test results on untreated grab leachate samples show high concentration of TDS (734 ppm), COD (1631 ppm), NH4 +-N (1253 ppm), HCO3 - (27962 ppm) and certain heavy metals such as Ni (1.05 ppm) and Cr (0.74 ppm) and have very high potential for contaminating ground and surface water. Biological treatment through aeration and sedimentation improves the quality of leachate significantly. However, parameters such as COD (1437 ppm) are found to be still high even after treatment. The surface water samples around the landfill site appear to be contaminated, most probably, through the overflow of leachate. Groundwater parameters, however, satisfy drinking water quality standard except, the concentration of NH4 +-N (maximum 74.2 ppm) and K (maximum 25 ppm). Key words: Leachate; Pollution; Solid waste; Landfill DOI: http://dx.doi.org/10.3329/jbas.v35i2.9418 JBAS 2011; 35(2): 153-160